2000
DOI: 10.1007/s004200000190
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment to concentration-dilution of spot urine samples: correlation between specific gravity and creatinine

Abstract: Results confirm the gender-dependence of creatinine concentrations in spot specimens and also show age-dependence, indicating the need for these aspects to be considered when the range of acceptable samples is to be set. No significant intra- or inter-day variations were observed for the two parameters. Lastly, the possibility of a comparison of differently adjusted values was indicated by a conversion formula derived from adjustments to creatinine and the corresponding specific gravity of a hypothetical urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
72
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 12 publications
15
72
1
Order By: Relevance
“…Kesteloot and Joossens (18 ) reported a mean CR clearance of ϳ101 mL/min in 2075 men and 86.9 mL/min in 1933 women. This and other studies (36,37 ) also showed a decrease in CR clearance with age, leading to increased serum and decreased urinary concentrations at older ages, making CR correction particularly questionable for adjusting urinary hormone values in research concerning aging, such as the transition to menopause.…”
Section: Discussionmentioning
confidence: 65%
“…Kesteloot and Joossens (18 ) reported a mean CR clearance of ϳ101 mL/min in 2075 men and 86.9 mL/min in 1933 women. This and other studies (36,37 ) also showed a decrease in CR clearance with age, leading to increased serum and decreased urinary concentrations at older ages, making CR correction particularly questionable for adjusting urinary hormone values in research concerning aging, such as the transition to menopause.…”
Section: Discussionmentioning
confidence: 65%
“…In particular, specific gravity depends on the degree of hydration and urinary solutes. Therefore, in the antidoping field, as in occupational medicine, adjustment for specific gravity and/or urinary creatinine concentration is currently performed (46 ). Consequently, for calculation of the urinary concentrations of the nandrolone metabolites, the following formula is applied by the majority of antidoping laboratories to correct values for samples for which the specific gravity is Ͼ1.020 (47 ):…”
Section: Discussionmentioning
confidence: 99%
“…Concentrated urine was defined as that with creatinine concentrations of Ͼ200 mg/dL for mothers, Ͼ128 mg/dL for 1-and 2-year-old children, and Ͼ150 mg/dL for 3-year old children. 36 …”
Section: Secondary Analysesmentioning
confidence: 99%